A mathematical model for the influence of the anti-friction material on friction. Issue 14 (1st November 2016) - Bian, Da; Zhao, Yongwu
Abstract: A mathematical model for the influence of the anti-friction material on friction is presented. The predictions of the model are compared with the experimental results and show good agreements. In addition, the predictions of the present model indicate that the friction coefficient initially decreases with the increase in the normal force and follows by a plateau. For sufficiently small normal loads, the friction coefficient with anti-friction material has no difference with that without anti-friction material. And then, the difference between them increases with the increase in the normal force and the friction coefficient with anti-friction material is smaller than that without anti-friction material. With the further increase in the normal force, the difference begins to level off. This study provides some insights into friction material designing.